Metodologi Pemahaman Hadis Edi Safri - muhammad sabri aliamran (Jurnal Ulunnuha, 2021)
From classical to contemporary times the method of understanding of the hadith has always develoved by looking at the context of the method of understanding the hadith in view of an essential in understanding the intent and wearing teh hadith, for the hadith is a reference to islamic law. Furthermore, Sometimes there is an error in the middle of ummah, which is due to lack of understanding of the metodhology of understanding the hadith. Pofessor Edi Safri ia a contemporary scholar wo studies the hadith. The Studi aims to exsplore the methologi of understanding the hadith according to professor Edi Safri and his contemporary conversion. As for the risearch method in this matter, it uses the libabry risearch method with a descrivtipe qualitative approach. Furthermore, the findings in this study are, teh tipology of teh Edi Safri understanding of the hadith ia textual and contextual. the textual meaningis to understand the hadiths based on the text itself or to compare eith other text. Whereas contextual he intended was to tex the hadith bay subtantiating tehm with nothing further tahn zahir’s own meaning, he differed fro, a contemporary cleric of hadith who had come to understand them with a confirmation of scientific truth and historical fact.